2015
DOI: 10.1017/s0967199414000793
|View full text |Cite
|
Sign up to set email alerts
|

Number of embryos biopsied as a predictive indicator for the outcome of preimplantation genetic diagnosis by fluorescence in situ hybridisation in translocation cases

Abstract: This study aimed to investigate the optimum number of embryos to be biopsied in order to increase the likelihood of obtaining a balanced/normal embryo following preimplantation genetic diagnosis (PGD) by fluorescence in situ hybridisation (FISH) for translocation carriers. Patients with low number of fertilised oocytes (≤5) or low number of embryos available for PGD (<7) underwent multiple hormonal stimulation cycles and their embryos from each cycle were vitrified and accumulated to obtain at least three embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Recent studies support this conclusion, as clinical pregnancy and live birth rates have been shown to increase according to the number of eggs retrieved [20] and oocytes fertilized [21]. Consequently, the probability of nding at least one euploid embryo increases with the number of oocytes retrieved [22] and embryos biopsied [23]. The blastocyst cohort size is also associated with at least one euploid embryo being found [24].…”
Section: Discussionmentioning
confidence: 87%
“…Recent studies support this conclusion, as clinical pregnancy and live birth rates have been shown to increase according to the number of eggs retrieved [20] and oocytes fertilized [21]. Consequently, the probability of nding at least one euploid embryo increases with the number of oocytes retrieved [22] and embryos biopsied [23]. The blastocyst cohort size is also associated with at least one euploid embryo being found [24].…”
Section: Discussionmentioning
confidence: 87%
“…In the past, one of the main problems of performing blastocyst biopsy was the limited time allowed for the diagnosis since the embryonic cells are either biopsied on day 5 or on day 6 for the slow developing embryos. With the use of vitrification, high embryo survival rates were reported [77][78][79][80], and many centers have opted performing PGS at blastocyst stage [81]. Furthermore, vitrifying embryos provide chance of an embryo transfer during an unstimulated cycle that was shown to result in high pregnancy rates [82][83][84].…”
Section: Numerical Chromosomal Abnormalities In Embryos and Preimplanmentioning
confidence: 99%